Cost and generic prescription analysis of psychotropic prescriptions in psychiatric OPD of a rural tertiary care teaching hospital - Wagle, L.; Kumaraswamy, M.; Bajracharya, M. (Journal of Manmohan Memorial Institute of Health Sciences, 2018)
Background: There is increased interest on cost utilisation of psychotropic drugs in recent years. Objective of this study was to perform cost and generic prescription analysis of psychotropics in psychiatric outpatient department at tertiary care teaching hospital.Methods: This was cross sectional, observational and uni-centric study of 6 month duration which was performed at Psychiatric Outpatient Department at one of the tertiary care hospital, Karnataka India. Cost analysis of prescriptions containing at least one psychotropic drug was performed based on cost/defined daily dose method from hospital perspective. Direct drug cost of psychiatric illness per day and pattern of generic prescribing were also studied. The data was analysed & summarised as mean, frequency, percentage (%), standard deviation (SD), and chi square test( at 95% confidence level) as appropriate using Microsoft excel and Graph Pad InStat statistical software.Results: We observed 15 different types of psychotropics among 101 prescriptions that was reviewed. Most expensive psychotropic was Divalproex whereas Clonazepam was the cheapest one. Most money was spent by hospital on Sertraline (24.19%) and least on Lithium (1.92%). Most expensive therapeutic categories were antidepressants (32.39%) followed by mood stabilisers (27.06%), antipsychotics (24.77%) and sedative/hypnotics (15.76%). Among different antidepressants; Amitriptyline was cheaper option and Mirtazepine was expensive. Likewise Quetiapine was expensive and Risperidone was cheaper among antipsychotics. Zolpidem and Divalproex were expensive sedative/hypnotic and mood stabilisers respectfully. Most expensive psychiatric illness was found to be bipolar disorder (Rs 20.53±12.84). 19 out of 147 were prescribed with generic names.Conclusion: The cost burden due to psychiatric drugs is high. Expensive and cheaper psychotropic for psychiatric OPD were Divalproex and Clonazepam respectively. Expensive therapeutic category was found to be antidepressants. From hospital perspective much money was spent on Sertraline and less on Lithium respectively. Similarly high cost of illness was observed in bipolar disorder and less in dissociative disorder. Generic name prescribing is very less.JMMIHS.2018;4(1):43-54